Pelatihan produksi pakan buatan skala rumah tangga untuk pembudidaya ikan di kota Sorong, Papua Barat - Mohammad Sayuti; Iman Supriatna; Agung Setia Abadi; Intanurfemi B. Hismayasari; Ernawati Ernawati; Saidin Saidin (Penerbit Goodwood, 2021)
Purpose: This community service aimed to train fish farmers in Sorong City to produce artificial feed containing 30% feed protein . Methods: The methods implemented were lectures and direct practice of making fish diets. Pearson square method was used for the feed formulation. Results: The output of this dedication activity increased the knowledge and expertise of fish farmers to make fish feed independently so that farmers can save operational costs in farming activities. Conclusions: This activity was attended by 10 participants and all participants could understand the concept of the training and be able to make artificial fish feed independently. Keywords: Fish feed, Pearson square, Fish Farmer, Training